Ephemeral temporal partitioning may facilitate coexistence in competing species. (April 2019) - Sovie, Adia R.; Greene, Daniel U.; Frock, Catherine F.; Potash, Alex D.; McCleery, Robert A.
Abstract : Animals change their daily activity patterns in response to season, food availability and the presence of competitors. Competition may be an important driver of a species' daily activity pattern, as animals manage conflict by avoiding each other temporally. We evaluated how vegetation structure and the presence of competitors changed the daily activity patterns of closely related fox squirrels, Sciurus niger, and grey squirrels, Sciurus carolinensis . We monitored squirrel activity in north and central Florida using passive game cameras at two spatial scales: local and point. To understand how seasonality and competition interact to drive behaviour, we compared squirrel activity during the leaf-off (1 January – 15 March) and leaf-on (16 March – 1 July) seasons. We tested for a relationship between squirrel activity and canopy cover by fitting a von Mises kernel distribution. To test how season and competition affected squirrel behaviour, we compared activity by computing a kernel density overlap function, ranging from 0 (no overlap: the squirrels are never active at the same time) to 1 (complete overlap: the squirrels have identical activity patterns). We found that daily squirrel behaviour was not influenced by canopy cover ( P  = 0.61). Fox squirrels had a single activity peak occurring around midday. In contrast, grey squirrels had a bimodal activity pattern with peaks shortly after sunrise and before sunset. The intensity of this partitioning existed on a gradient and changed with season and the presence of competitors. Fox and grey squirrel daily patterns overlapped the most when they were allopatric in the leaf-on season (overlap = 0.70, P < 0.001) and the least while sympatric in the leaf-on season (overlap = 0.24, P < 0.08). This ephemeral response to competition highlights that various axes of resource partitioning can promote coexistence between closely related species. Highlights: We examined daily activity patterns of competing grey and fox squirrels. Squirrel behaviour was not influenced by canopy cover. Fox squirrels had a single activity peak around midday. Grey squirrel activity peaked shortly after sunrise and before sunset. Temporal partitioning existed on a gradient and varied with season and competition.